Foundations of ambiguity and economic modeling - Mukerji, S (University of Oxford, 2009)
Are foundations of models of ambiguity-sensitive preferences too flawed to be usefully applied to economic models? Al-Najjar and Weinstein (2009) say such is indeed the case. In this paper, first, we point out that many of the key arguments by Al-Najjar and Weinstein do not apply to quite a few of the ambiguity preference models of more recent vintage, and therefore to that extent do not undermine the foundational aspects or applicability of ambiguity models in general. Second, we argue the focus in that paper on Ellsberg examples is an overly narrow concern; the Ellsberg examples have their uses but they are not the best context to understand why reasonable real-world agents may find acting with ambiguity-sensitive preferences normatively or prescriptively appealing. Finally, normative considerations aside, we submit that Al-Najjar and Weinstein are unduly dismissive of the power of such preferences to provide illuminating positive analyses of economic phenomena.